Bioaccessibility study of plant sterol-enriched fermented milks. Issue 1 (8th October 2015) - Vaghini, Silvia; Cilla, Antonio; Garcia-Llatas, Guadalupe; Lagarda, María Jesús
Abstract : The bioaccessibility (BA) of total and individual plant sterols (PS) of four commercial PS-enriched fermented milk beverages (designated as A to D) was evaluated using in vitro gastrointestinal digestion including the formation of mixed micelles. Abstract : The bioaccessibility (BA) of total and individual plant sterols (PS) of four commercial PS-enriched fermented milk beverages (designated as A to D) was evaluated using in vitro gastrointestinal digestion including the formation of mixed micelles. The fat content of the samples ranged from 1.1 to 2.2% (w/w), and PS enrichment was between 1.5 and 2.9% (w/w). β-Sitosterol, contained in all samples, was higher in samples A and B (around 80% of total PS). The campesterol content was C (22%) > A (7%) > B (5%). Sitostanol was the most abundant in sample D (85%). Stigmasterol was only present in sample C (33%). The greatest BA percentage for total PS corresponded to samples A and B (16–17%), followed by sample D (11%) and sample C (9%). The total BA was not related to the protein, lipid or PS content of the beverages, whereas samples with higher carbohydrates and fiber contents showed lower BA. The BA of the individual PS differed according to the sample considered, and was not related to the PS profile of the sample, thus indicating strong dependency upon the matrix (PS ingredient and other components). Although in vivo studies should be carried out to better assess the functionality of PS in functional foods such as enriched fermented milk beverages, our in vitro study is a useful preliminary contribution to evaluation of the efficacy of these products.